Five Scots Pine Orthologues to QTLs Associated with Resistance Against H. parviporum in Norway Spruce - Bengtsson, Emil (2020)
Heterobasidion annosum s.l. (sensu lato, in the broad sense) is a fungal complex consisting of five partly intersterile species and is regarded as the most devastating forestry pest in the northern hemisphere. The fungus is specialized on coniferous trees and utilizes lignin, cellulose and other structural compounds of the wood as its nutrient source. Infection by the fungus results in rotted wood, stunted growth and in death of the host. The fungus wood-decaying properties also results in timber unsuitable as construction material. H. annosum s.l. has a large economic impact on the forestry industry, causing annual losses estimated to exceed €1 billion in the EU alone. Scots pine, an economical important tree species, is infected by H. annosum s.s. (sensu stricto, in the narrow sense). There have been some studies of breeding Scots pine for enhanced resistance to H. annosum s.s., but surprisingly little is known about this topic. Several quantative trait loci (QTLs) associated with resistance to H. parviporum – one of the species within the complex – in Norway spruce were recently identified. This thesis investigated if those loci also existed in the Scots pine genome. Five orthologues to the QTLs were successfully identified in genotypes present in the Swedish forest tree breeding programme. Four out of the five genes possessed SNPs, suggesting that there might be genetic potential for breeding future Scots pine trees with enhanced resistance to the pathogen. Field inoculation of H. annosum s.s. failed to detect any significant variation in resistance between the different Scots pine genets although there was a clear trend (p-value = 0.054). Future studies could potentially identify variation in resistance of the Scots pine genotypes and associate the phenotypic variation with variants of the QTL orthologues identified in this thesis.